2017
DOI: 10.1089/dia.2017.0235
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Applications Among Adults with Type 1 and Type 2 Diabetes: Results from the Second MILES—Australia (MILES-2) Study

Abstract: A minority of adults with T1D and T2D use apps to support their self-management. App use among adults with T1D is associated with a more recent T1D diagnosis, more frequent glucose monitoring, and lower self-reported HbA1c. Future efforts should focus on this association and determine the mechanisms by which app use is related to better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
83
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 33 publications
13
83
1
1
Order By: Relevance
“…Younger adults have a higher level of digital literacy. This is in line with other studies which found higher levels of app use in younger populations [57,62,63]. Possibly, it might also be due to the improved awareness of the consequences of failing to monitor blood glucose levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Younger adults have a higher level of digital literacy. This is in line with other studies which found higher levels of app use in younger populations [57,62,63]. Possibly, it might also be due to the improved awareness of the consequences of failing to monitor blood glucose levels.…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes app use in this study was higher than reported from other studies. For example, a study conducted in New Zealand reported a use of 20% among people with type 1 diabetes [46], another study conducted in Australia reported user rates of 24% for persons with type 1 DM and 8% for persons with type 2 DM [57]. It was also much higher than user rates reported in studies from the US (4%) [22] and Scotland (7%) [58].…”
Section: Discussionmentioning
confidence: 99%
“…A survey by Boyle et al revealed that the most favored feature of patients was a glucose diary, and an insulin calculator was the most desirable function for a future app [22]. A survey by Trawley et al showed carbohydrate counting was the most common purpose among adults with T1DM and glucose monitoring was the most common purpose among adults with T2DM [23]. A recent meta-analysis of diabetes apps revealed that the reduction in HbA 1c is explained by the frequency of HCP feedback [18].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin dosing for carbohydrate, fat and protein is significantly more complex than determining the insulin dose for carbohydrate alone. Previous studies have demonstrated that smartphone applications, with the support of dedicated health professionals, can reduce insulin dose errors, support diabetes self‐management and improve glycaemic control . Therefore, an insulin‐dosing application may be a helpful tool to guide complicated adjustments regarding insulin bolus amount and delivery options for foods of mixed macronutrient composition.…”
Section: Discussionmentioning
confidence: 99%